Electrochemical Construction of C–S Bond: A Green Approach for Preparing Sulfur-Containing Scaffolds - Zou, Ruonan; Yu, Jingbo; Ying, Ping (Pharmaceutical Fronts, 2024)
The organosulfur frameworks containing C–S bonds are important structural motifs in various biologically active molecules and functional materials. In this regard, transition-metal catalysis using chemical oxidants to prime reactions has emerged as the most common method, however, is prone to several side reactions such as dimerization and overoxidation. In recent years, organic electrosynthesis has become a hot topic due to its eco-friendly and mild process in which costly catalysts and toxic oxidants could be replaced by electrons. This perspective summarized the recently developed C–S bond electrosynthesis protocols, discussing and highlighting reaction features, substrate scope, as well as its application in pharmaceuticals, and the underlying reaction mechanisms. The study helps the development of electrochemical process-enabled C–S bond construction reactions in the future.
Keywords: electrochemical; sulfur-containing compounds; C–S bond